An analysis of the deployment of synergistic cyber security awareness model for the elderly (SCSAM-Elderly) in Malaysia - Nurul Alieyah Azam,; Alya Geogiana Buja,; Rabiah Ahmad,; Shekh Faisal Abdul Latip,; Nor Masri Sahri, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study explores the deployment analysis of the Synergistic Cyber Security Awareness Model for the Elderly (SCSAM-Elderly) in Malaysia. The incidence of cyber security events has been steadily increasing, particularly affecting the elderly demographic. The SCSAM-Elderly has been developed to address persistent challenges posed by cybercrimes, such as phishing, romance scams, and identity theft, with the primary objective of educating and heightening awareness among the elderly. Designed to be user-friendly and tailored for the elderly population, the SCSAM-Elderly aims to enhance their awareness. The study's objective is to analyze the pre-survey and post-survey data collected from elderly individuals in Malaysia using SPSS to confirm and validate the effectiveness of the SCSAM Elderly model. Surveys were distributed to 50 elderly individuals in Melaka, and the data were analyzed using SPSS Version 27.0. This study employed a paired sample t-test, a statistical method used to determine if there is a significant difference between the average scores of two related groups. In this study, the two groups are the pre-survey and post survey scores from the same participants. The results indicated that the SCSAM-Elderly model showed a significant increase in awareness after the implementation of cybersecurity training compared to before the training. The findings indicate that elderly individuals who underwent cyber security awareness training using this model demonstrated an improved ability to detect and counteract the impacts of cybercrimes. The novelty of this study lies in being the first cybersecurity awareness model focusing on the elderly with less technicality.